Lexical-Semantic Features of Synonyms in The Language of Karakalpak Folk-Tales - Sh.M.Kunnazarova (Zien Journals, 2023)
This article talks about synonyms used in the language of Karakalpak folk tales, their formation, lexical and stylistic peculiarities, the service of artistic language in providing emotional-expressive color.
Keywords: semantics; synonym; polysemantic word